Estimating the size of the underground economy in the UAE: Evidence from Gregory-Hansen cointegration based currency demand approach - Mohammed Gamal, Awadh Ahmed; Dahalan, Jauhari (Society of Interdisciplinary Business Research, 2015)
The paper estimates the size of the underground economy and tax evasion in the UAE over the period of 1991:1-2010:4. The study based on currency demand approach model as a proxy to measure the underground economy.The results indicate that the size of the underground economy in the UAE grew significantly on average of 10.34% of the GDP over the study period. The rate of tax evasion on the non-oil tax revenues reached, on average, 10.34% over the study period. Nevertheless, the rate of tax evasion to the GDP remained, on average, at its lowest level at 0.63%.